Hereditary Rolandic Epilepsy and Speech Dyspraxia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
A syndrome of nocturnal oro-facio-brachial partial seizures, secondarily generalized partial seizures, centro-temporal epileptiform discharges, associated with oral and speech dyspraxia and cognitive impairment, is described in a family of 9 affected members in three generations reported from Austin Hospital, Heidelberg (Melbourne), the University of Melbourne, and the Royal Children's Hospital, Melbourne, Australia.